2017
DOI: 10.3390/ijms18071413
|View full text |Cite
|
Sign up to set email alerts
|

An In Vitro Potency Assay for Monitoring the Immunomodulatory Potential of Stromal Cell-Derived Extracellular Vesicles

Abstract: Abstract:The regenerative and immunomodulatory activity of mesenchymal stromal cells (MSCs) is partially mediated by secreted vesicular factors. Extracellular vesicles (EVs) exocytosed by MSCs are gaining increased attention as prospective non-cellular therapeutics for a variety of diseases. However, the lack of suitable in vitro assays to monitor the therapeutic potential of EVs currently restricts their application in clinical studies. We have evaluated a dual in vitro immunomodulation potency assay that rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
80
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 75 publications
(85 citation statements)
references
References 36 publications
5
80
0
Order By: Relevance
“…We therefore plan a more detailed analysis, particularly of the immune-related proteomic profile of EVs vs. donor cells vs. soluble factors, and validation of results in additional experimental models towards rational potency-based selection of cell-and EVbased therapeutics. This will include comprehensive genomic analysis focusing on small RNA species as initiated previously in a study for monitoring the immunomodulatory potential of neonatal umbilical cord stromal cell-derived EVs [18]. Our quantitative EV purification approach will also allow for combining lipidomics, glycomics and metabolomics for a more broad view on PLX-EV biology using upcoming technology [35]- [37].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We therefore plan a more detailed analysis, particularly of the immune-related proteomic profile of EVs vs. donor cells vs. soluble factors, and validation of results in additional experimental models towards rational potency-based selection of cell-and EVbased therapeutics. This will include comprehensive genomic analysis focusing on small RNA species as initiated previously in a study for monitoring the immunomodulatory potential of neonatal umbilical cord stromal cell-derived EVs [18]. Our quantitative EV purification approach will also allow for combining lipidomics, glycomics and metabolomics for a more broad view on PLX-EV biology using upcoming technology [35]- [37].…”
Section: Discussionmentioning
confidence: 99%
“…We next devised a standardized high content process for EV production (Fig.1) based on previous results [18]. Large volumes of fibrinogen-depleted -MEM* (n x 500 mL) were first depleted for platelet-rich plasma-and serum-derived particles (including EVs) before use in large-scale PLX culture ( Fig.1A).…”
Section: Physically Defined Media Enable Efficient Cell-derived Ev Chmentioning
confidence: 99%
See 1 more Smart Citation
“…Exosomes carry complex cargo including proteins, lipids and nucleic acids, and transfer them to recipient cells to exert function. MSC-derived exosomes (MSC-exo) are reportedly capable of mimicking most biological functions of MSCs including anti-inflammatory and anti-apoptotic effects and can increase levels of anti-inflammatory cytokines, decrease levels of proinflammatory cytokines [18,19], and inhibit activation of astrocytes [17] and macrophages [20]. Similar to MSCs, MSC-exo infusion can inhibit NFκB activation [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…The literature is controversial regarding the effects of MSC-EVs on lymphocyte proliferation. Some studies have shown inefficiency of MSC-EVs in inhibiting T cell proliferation [52][53][54], others have demonstrated lower efficiency of EVs when compared to MSCs [55][56][57][58] while others have reported ability to inhibit lymphocyte proliferation [59][60][61]. The difference between these studies may be due to variations in the dose and types of EVs and T cell sources used.…”
Section: Discussionmentioning
confidence: 99%